China's Slowdown and Global Financial Market Volatility : Is World Growth Losing Out? - Cashin, Paul (IMF Working Papers; Working Paper ;, 2016)
China's GDP growth slowdown and a surge in global financial market volatility could both adversely affect an already weak global economic recovery. To quantify the global macroeconomic consequences of these shocks, we employ a GVAR model estimated for 26 countries/regions over the period 1981Q1 to 2013Q1. Our results indicate that (i) a one percent permanent negative GDP shock in China (equivalent to a one-off one percent growth shock) could have significant global macroeconomic repercussions, with world growth reducing by 0.23 percentage points in the short-run; and (ii) a surge in global financial market volatility could translate into a fall in world economic growth of around 0.29 percentage points, but it could also have negative short-run impacts on global equity markets, oil prices and long-term interest rates.